Divided Over Thaksin Thailand's Coup and Problematic Transition - Funston, John (ISEAS Publishing, 2009)
Thailand's political problems attracted international attention when yellow shirted anti-Thaksin protestors closed down Bangkok's international airports in November 2008; the following April pro-Thaksin red shirts prevented an ASEAN-East Asia Summit, and clashed violently with the army in the streets of Bangkok. Conflict between groups for and against former Prime Minister Thaksin has polarized Thai society. Under his watch, violence also returned to the Malay Muslim south, with the loss of over 3,000 lives. The military coup that ousted Thaksin was supposed to end all this, but instead polarization increased and southern violence continued. This book is about how Thaksin divided Thailand, the nature of the southern conflict, and problematic attempts to establish a consensus around a post-Thaksin political order